Inflammation Directs Memory Precursor and Short-Lived Effector CD8(+) T Cell Fates via the Graded Expression of T-bet Transcription Factor - Joshi, Nikhil S. (2007)
As acute infections resolve, effector CD8 T cells differentiate into IL-7R(lo) short-lived effector cells (SLECs) and IL-7R(hi) memory precursor effector cells (MPECs) capable of generating long-lived memory CD8 T cells. Using another SLEC marker, KLRG1, we found that KLRG1(hi) effector cells began appearing early during infection and were committed to downregulating IL-7R. Unlike IL-7R(hi) MPECs, KLRG1(hi) IL-7R(lo) SLECs relied on IL-15, but IL-15 could not sustain their long-term maintenance or homeostatic turnover. The SLEC/MPEC fate decision was regulated by the amount of inflammatory cytokines (i.e. IL-12) present during T cell priming. According to the amount of inflammation, a gradient of T-bet was created in which high T-bet levels induced SLECs and low levels promoted MPECs. These results elucidate a novel mechanism by which the innate immune system sets the relative levels of a lineage-determining transcription factor in activated CD8 T cells and correspondingly, regulates their memory cell potential.